Affordances of wikispaces for collaborative learning and knowledge management - Amreet Kaur Jageer Singh; Raja Nor Safinas Raja Harun; Wan Fareed (Penerbit UKM, 2013)
A wiki, namely, Wikispaces is a component of Web 2.0 technology tools. It is utilised as a peer editing platform for students in correcting errors made by them in their essay writing. The purpose of this article is to find out how the affordances of Wikispaces encourage collaborative learning and knowledge management in correcting errors in L2 students‟ essays. The experience of using Wikispaces throughout the peer editing context and its affordances are described extensively based on three perspectives: pedagogical, social and technological. Data was obtained from online-writing records (students‟ essays), field notes, questionnaire, reflective research diary, and feedback form. The qualitative data are analysed thematically and then triangulated. In terms of pedagogical affordances, Wikispaces supports dual applications of pedagogical approaches (teaching and learning). In relation to social affordances, Wikispaces promotes a variety of interactions (peer-peer and students-teacher interactions) and the dynamics of the activities involved (individual, group and whole-class work) provide a safe and comfortable environment for social interaction and add possibility for asynchronous communications to happen through discussion forums and personal messaging. With respect to the technological affordances, it is a free, user-friendly, and easily accessible web-based tool provided via the Internet. Wikispaces secures backups as well as supports flexible learning environment with the presence of two features: page reverting and autosave. This study implicates the needs to consider the three mentioned affordances of wikis (pedagogical, social and technological) as a platform for teaching and learning.